A Targeted RNAi Screen Identifies Novel Regulators of Synapse Formation and Function - Carpenter, Nathan (My University, 2015)
An intricate knowledge of synapse formation and regulation is crucial to understanding how neurons develop, interact, and grow. In an attempt to gain a deeper comprehension of synapse development, we performed a three-part genetic screen using Gal-4 driven RNAi in Drosophila melanogaster and identified four novel genes, which might play crucial roles in synapse formation and function. The four genes each displayed two of the following phenotypes: abnormal morphology at neuromuscular junction four, abnormal synaptic transmission in the retina, or abnormal locomotion behavior. These genes,CG 14010, CG31708, CG8909, and CG8500 represent a diverse class of molecules. CG 8500 is a Di-Ras protein, which is suggested to play a role in ADHD. CG8909 is a lowdensity lipoprotein-related protein 4 (LRP4) and may function in congenital myasthenic syndrome. Both CG14010 and CG31708 are members of the neurotimin family, which has been associated with Alzheimer's.